Mudanças no padrão de metilação do DNA na progressão do melanoma - Rius, Flavia Eichemberger [UNIFESP] (2020)
Melanoma is the cancer derived from melanocytes, cells located in the basal layer the epidermis which are responsible for melanin production. In Brazil there we 6,260 deaths by melanoma at 2018, with this being the skin cancer with highe number of deaths. In this work, a model constituted by cell lineages correspondent different stages of melanoma progression was used to disclose DNA methylati marks which could characterize each stage. The experiment called ERRB (Enhanced Reduced Representation Bisulfite Sequencing) was realized to access methyl cytosines in CpG context in the cell lines, at base pair level. Methylati states were analyzed in malignant transformation of melanocytes as well as acquisition of metastatic capability of melanoma. In melanoma maligna transformation it was observed biggest hypomethylation in genic promoters, whilst melanoma metastatization it was observed significant hypermethylation in tho regions. The analysis of regulatory capability of those genic promoters showed th hypomethylated promoters have an important relationship to regulation of ge expression for ransformation signature as well as for metastatization of melanom signature. Genes which present hypomethylated promoters in maligna transformation signature as well as in metastatization signature enrich for pathwa related to embryonic development, specially of return to epigenetic a transcriptional state of neural crest cells. Hypermethylated promoters we associated to cell membrane regulation in the signature of melanom metastatization. Using TCGA data, multivariate analyses of ten of the gen identified in this study show correlation between the level of methylation and surviv of patients with melanoma for four genes, namely NEFM, PLXNB1, SEMA7A a SYT5. Analysis of the methylome of cell lineages composing the model of study h provided a great amount of data, which could still be explored to identify not on new biomarkers for prognostic, but also to disclose mechanisms involved malignant transformation of melanocytes as well as in melanoma progression.